2022
DOI: 10.3389/fimmu.2022.946350
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 Polymorphisms as Risk Factors for Progression to Chagas Disease Cardiomyopathy: A Case-Control Study and Meta-Analysis

Abstract: BackgroundChagas disease is a lifelong infection caused by the protozoa Trypanosoma cruzi endemic in Latin-America and emergent worldwide. Decades after primary infection, 20-30% of infected people develop chronic Chagas cardiomyopathy (CCC) while the others remain asymptomatic. CCC pathogenesis is complex but associated with sustained pro-inflammatory response leading to tissue damage. Hence, levels of IL-10 could have a determinant role in CCC etiology. Studies with Latin-American populations have addressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…In the chronic phase of Chagas disease, IL-10 participates in delaying the onset of chronic Chagas heart disease (CCD) in infected individuals. A comprehensive analysis of the cytokine profile revealed that the decrease in IL-10 levels shifts the immune response from the anti-inflammatory profile of asymptomatic patients to that of cardiac patients [ 11 ]. Considering the anti-inflammatory potential of the compound in macrophage cell lines, we decided to evaluate the secretion capacity of IL-10 as an immunoregulatory cytokine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the chronic phase of Chagas disease, IL-10 participates in delaying the onset of chronic Chagas heart disease (CCD) in infected individuals. A comprehensive analysis of the cytokine profile revealed that the decrease in IL-10 levels shifts the immune response from the anti-inflammatory profile of asymptomatic patients to that of cardiac patients [ 11 ]. Considering the anti-inflammatory potential of the compound in macrophage cell lines, we decided to evaluate the secretion capacity of IL-10 as an immunoregulatory cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the anti-inflammatory cytokine IL-10 is involved in delaying the onset of CCC in infected individuals. A comprehensive analysis of the cytokine profile has revealed that a reduction in IL-10 levels alters the immune response from the anti-inflammatory profile seen in asymptomatic patients compared to that observed in cardiac patients [ 11 ]. In this sense, modulating the inflammatory response in individuals with Chagas disease could have therapeutic potential [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent case-control study and meta-analysis identified an IL-10 polymorphism, the genotype TT at -819 rs1800871, as a contributor to genetic susceptibility in chronic cardiac cardiomyopathy, making this polymorphism a suitable candidate to be included in a panel of predictive biomarkers of disease progression (Grijalva et al 2022 ). These genetic variations in the IL-10 gene promoter induce high IL-10 production (Grijalva et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In various infectious diseases, rs1800871C and/or rs1800872C is reportedly associated with the onset of chronic infections: a decreased susceptibility to tuberculosis ( Yu et al, 2019 ; Chen and Ma, 2020 ), increased susceptibility to leprosy ( Cardona-Castro et al, 2012 ; Dos Santos et al, 2021 ), decreased susceptibility to herpes zoster ( Haanpää et al, 2002 ), and increased susceptibility to HBV infection ( Ye et al, 2020 ). These alleles are also associated with the course, progression, response to therapy and outcome: a better outcome of leprosy ( Alvarado-Arnez et al, 2015 ), low infection intensity of Schistosoma mansoni in schistosomiasis ( Mewamba et al, 2023 ), reduced risk of cardiomyopathy in Chagas disease ( Grijalva et al, 2022 ), reduced risk of anemia in newborns in Plasmodium falciparum malaria infection ( Lokossou et al, 2013 ), increased risk of Epstein–Barr virus (EBV)-associated hemophagocytic lymphocytosis ( Tang et al, 2021 ), reduced risk of breast cancer after EBV infection ( He et al, 2012 ), increased risk of AIDS-related non-Hodgkin lymphoma ( Wong et al, 2010 ), increased risk of progressive liver disease in chronic hepatitis B ( Miyazoe et al, 2002 ), reduced chance of seroclearance after antiviral treatment of chronic hepatitis B ( Rybicka et al, 2020 ), poor reduced disease severity of chronic hepatitis C ( Świątek-Kościelna et al, 2017 ), and reduced risk of hepatocellular carcinoma in chronic hepatitis C ( Aroucha et al, 2016 ; Sghaier et al, 2017a ). For acute infections, s1800871C and/or rs1800872C is reportedly associated with a decreased risk of dengue infection ( Eloisa Monroy-Muñoz et al, 2023 ) and dengue hemorrhagic fever ( Alagarasu et al, 2015 ), decreased risk of asthma after bronchiolitis in infancy ( Korppi et al, 2017 ), and reduced severity (requiring admission to intensive care unit) of sepsis ( Montoya-Ruiz et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%